Relative Motion Control System of Spacecraft for Contactless Space Debris Removal - Khoroshylov, S.V. (Science and Innovation, 2024)
Introduction. The research deals with the development of a spacecraft control system for contactless space debris removal using the “ion beam shepherd” technology. Such a system is necessary to provide conditions for effective transfer of decelerating impulse to a space debris object by ion beam in the deorbiting phase. Problem Statement. The design and analysis of the system has to be carried out taking into account the ion beam effects, a wide range of orbital disturbances, inaccuracies in determining the relative position and implementing the control actions, time-varying and parametric uncertainty, and limitations on the control actions. Purpose. The purpose is to design a system to control spacecraft relative motion for contactless space debris removal. Materials and methods. The mixed sensitivity approach is applied to the system design. The requirements for the controller are specified in the frequency domain using the selected weight functions. The structured singular values methodology is used to analyze the system robustness. Results. The system robustness and compliance with specified requirements have been confirmed both by a formal criterion and by computer simulation. A rational softening of the requirements for the control accuracy enables reducing significantly the propellant mass needed to maintain the relative position keeping an acceptable rate of space debris removal. Conclusions. The designed control system provides a compromise between robust stability, performance, and costs of control under the impact of a wide range of disturbances.